USING ROUND ROBIN TECHNIQUE TO IMPROVE TENTH GRADE STUDENTS’ SPEAKING SKILL OF SMK PERTANIAN PEMBANGUNAN NEGERI SEMBAWA - Nita Ria; Yuni Hartati (Didascein : Journal of English Education, 2021)
This research was aimed to find out whether or not there was any significant difference in speaking skill between the students’ who were taught by using Round Robin technique and those who were not. The population was all the tenth-grade student of SMK Pertanian Pembangunan Negeri Sembawa in the academic year 2019/2020 consisting of 130 students. The writers used purposive sampling technique in choosing the sample. There were 66 students of tenth grade students of SMK-PPN Sembawa involved in this study as the sample. They were divided into two groups, experimental and control groups, consisting of 33 students for each group. The method used quasi non-equivalent group design. Spoken test was used to collect the data.  Furthermore, the result of the data was analysed using independent sample t-test. The result showed that the mean score of experimental group increased from 70.88 in pre-test to 78.67 in post-test. The result of data analysis showed that the t-obtained was 2.625 and it was higher than t-table 1.9977. It meant that there was a significant difference between experimental and control group in speaking skill. The students who were taught using Round Robin technique could perform better in speaking skill than the students who were not taught using this technique. Keywords: Round Robin technique, speaking skill, descriptive text